Widespread non-target-site resistance in Setaria viridis to four classes of herbicide - Thomas H. Pendergast; Sailaja Maddali; Srinivasa R. Chaluvadi; Peng Qi; William K. Vencill; Jeffrey L. Bennetzen; Katrien M. Devos (Theoretical and Applied Genetics, 2026)
Key message Although herbicide resistance in Setaria is rampant and cosmopolitian across four herbicide families, we encountered little evidence of target-site resistance, indicating diverse non-target mechanisms of metabolizing, sequestering, and overwhelming herbicides. Abstract Setaria viridis is a cosmopolitan weed and model genetic system with increasing reports of resistance to multiple classes of herbicides. Our goal was to assess the herbicide resistance and allelic diversity in herbicide target genes in a collection of Setaria genotypes from North America and Eurasia, and identify the occurrence of novel and known target-site mutations that led to resistance. A total of 214 Setaria genotypes were exposed to commonly used herbicides that inhibit specific genes: herbicide action class (HRAC) group 1 herbicides targeting acetyl-CoA carboxylase (ACCase), HRAC 2 targeting acetolactate synthase (ALS), HRAC 9 targeting 5-enolpyruvylshikimate-3-phosphate (EPSP) synthase, and HRAC 10 targeting glutamine synthetase. ACCase and ALS genes in 53 accessions were PCR-amplified and sequenced. Whole-genome sequencing reads covering the target genes were analyzed for an additional 98 genotypes. Herbicide trials showed that 30% of our accessions set seed following application of at least one herbicide, and 13 accessions were resistant to multiple classes of herbicides. Although there were numerous SNPs, including some known to lead to resistance, in our target genes, SNPs found predominantly in herbicide-resistant genotypes were largely intronic or synonymous. A small number of amino acid substitutions in ALS and ACCase indicated potential and incomplete resistance to HRAC 1 and 2 herbicides, but no SNPs putatively associated with herbicide resistance were identified in the other 6 target-site genes. The broader pattern of herbicide resistance in S. viridis is likely driven by non-target mutations that detoxify or compartmentalize applied herbicides.

Mechanistic modeling of lipid nanoparticle (LNP) precipitation via population balance equations (PBEs) - Sunkyu Shin; Cedric Devos; Aniket Pradip Udepurkar; Pavan K. Inguva; Allan S. Myerson; Richard D. Braatz (Chemical Engineering Journal, 2025)

Impact of bacterial strain acquisition in the lung of patients with COPD: the AERIS study - Lucio Malvisi; Aparna Yarraguntla; Marie-Cécile Mortier; Karen Osman; David W. Cleary; Béatrice Sente; Thierry G. Pascal; Vincent Weynants; Stuart C. Clarke; Laura Taddei; Tom M. A. Wilkinson; Jeanne-Marie Devaster; et al. (Infectious Diseases, 2022)

Protected area characteristics that help waterbirds respond to climate warming - Elie Gaget; Alison Johnston; Diego Pavón‐Jordán; Aleksi S. Lehikoinen; Brett K. Sandercock; Alaaeldin Soultan; Luka Božič; Preben Clausen; Koen Devos; Cristi Domsa; Vitor Encarnação; Sándor Faragó; et al. (Conservation Biology, 2022)
Protected area networks help species respond to climate warming. However, the contribution of a site's environmental and conservation‐relevant characteristics to these responses is not well understood. We investigated how composition of nonbreeding waterbird communities (97 species) in the European Union Natura 2000 (N2K) network (3018 sites) changed in response to increases in temperature over 25 years in 26 European countries. We measured community reshuffling based on abundance time series collected under the International Waterbird Census relative to N2K sites’ conservation targets, funding, designation period, and management plan status. Waterbird community composition in sites explicitly designated to protect them and with management plans changed more quickly in response to climate warming than in other N2K sites. Temporal community changes were not affected by the designation period despite greater exposure to temperature increase inside late‐designated N2K sites. Sites funded under the LIFE program had lower climate‐driven community changes than sites that did not received LIFE funding. Our findings imply that efficient conservation policy that helps waterbird communities respond to climate warming is associated with sites specifically managed for waterbirds.

Benefits of protected areas for nonbreeding waterbirds adjusting their distributions under climate warming - Elie Gaget; Diego Pavón‐Jordán; Alison Johnston; Aleksi Lehikoinen; Wesley M. Hochachka; Brett K. Sandercock; Alaaeldin Soultan; Hichem Azafzaf; Nadjiba Bendjedda; Taulant Bino; Luka Božič; Preben Clausen; et al. (Conservation Biology, 2021)
Climate warming is driving changes in species distributions and community composition. Many species have a so‐called climatic debt, that is, shifts in range lag behind shifts in temperature isoclines. Inside protected areas (PAs), community changes in response to climate warming can be facilitated by greater colonization rates by warm‐dwelling species, but also mitigated by lowering extirpation rates of cold‐dwelling species. An evaluation of the relative importance of colonization‐extirpation processes is important to inform conservation strategies that aim for both climate debt reduction and species conservation. We assessed the colonization‐extirpation dynamics involved in community changes in response to climate inside and outside PAs. To do so, we used 25 years of occurrence data of nonbreeding waterbirds in the western Palearctic (97 species, 7071 sites, 39 countries, 1993–2017). We used a community temperature index (CTI) framework based on species thermal affinities to investigate species turnover induced by temperature increase. We determined whether thermal community adjustment was associated with colonization by warm‐dwelling species or extirpation of cold‐dwelling species by modeling change in standard deviation of the CTI (CTI SD ). Using linear mixed‐effects models, we investigated whether communities in PAs had lower climatic debt and different patterns of community change than communities outside PAs. For CTI and CTI SD combined, communities inside PAs had more species, higher colonization, lower extirpation, and lower climatic debt (16%) than communities outside PAs. Thus, our results suggest that PAs facilitate 2 independent processes that shape community dynamics and maintain biodiversity. The community adjustment was, however, not sufficiently fast to keep pace with the large temperature increases in the central and northeastern western Palearctic. Our results underline the potential of combining CTI and CTI SD metrics to improve understanding of the colonization‐extirpation patterns driven by climate warming.

Towards the European eradication of the North American ruddy duck - P. A. Robertson; T. Adriaens; A. Caizergues; P. A. Cranswick; K. Devos; C. Gutiérrez-Expósito; I. Henderson; B. Hughes; A. C. Mill; G. C. Smith (Biological Invasions, 2015)

Slowly progressive spinocerebellar ataxia with extrapyramidal signs and mild cognitive impairment (SCA21) - J. Delplanque; D. Devos; I. Vuillaume; A. De Becdelievre; E. Vangelder; C. A. Maurage; K. Dujardin; A. Destée; B. Sablonnière (The Cerebellum, 2008)

Allelic variation at the linked AP1 and PhyC loci in hexaploid wheat is associated but not perfectly correlated with vernalization response - J. Beales; D. A. Laurie; K. M. Devos (Theoretical and Applied Genetics, 2005)

An integrated genetic map and a new set of simple sequence repeat markers for pearl millet, Pennisetum glaucum - X. Qi; T. S. Pittaway; S. Lindup; H. Liu; E. Waterman; F. K. Padi; C. T. Hash; J. Zhu; M. D. Gale; K. M. Devos (Theoretical and Applied Genetics, 2004)

A linkage map of meadow fescue (Festuca pratensis Huds.) and comparative mapping with other Poaceae species - V. Alm; C. Fang; C. S. Busso; K. M. Devos; K. Vollan; Z. Grieg; O. A. Rognli (Theoretical and Applied Genetics, 2003)

Comparative analysis of QTLs affecting domestication traits between two domesticated × wild pearl millet (Pennisetum glaucum L., Poaceae) crosses - V. Poncet; E. Martel; S. Allouis; K. Devos; F. Lamy; A. Sarr; T. Robert (Theoretical and Applied Genetics, 2002)

Comparative genetic analysis of the Aegilops longissima and Ae. sharonensis genomes with common wheat - H. Zhang; S. M. Reader; X. Liu; J. Z. Jia; M. D. Gale; K. M. Devos (Theoretical and Applied Genetics, 2001)

Construction of a BAC library of pearl millet, Pennisetum glaucum - S. Allouis; X. Qi; S. Lindup; M. D. Gale; K. M. Devos (Theoretical and Applied Genetics, 2001)

Genetic control of domestication traits in pearl millet (Pennisetum glaucum L., Poaceae) - V. Poncet; F. Lamy; K. M. Devos; M. D. Gale; A. Sarr; T. Robert (Theoretical and Applied Genetics, 2000)

Comparative mapping reveals a complex relationship between the pearl millet genome and those of foxtail millet and rice - K. M. Devos; T. S. Pittaway; A. Reynolds; M. D. Gale (Theoretical and Applied Genetics, 2000)

Chromosome aberrations in wheat nullisomic-tetrasomic and ditelosomic lines - K. M. Devos; M. E. Sorrells; J. A. Anderson; T. E. Miller; S. M. Reader; A. J. Lukaszewski; J. Dubcovsky; P. J. Sharp; J. Faris; M. D. Gale (Cereal Research Communications, 1999)

Fifty new microsatellite loci for the wheat genetic map - P. Stephenson; G. Bryan; J. Kirby; A. Collins; K. Devos; C. Busso; M. Gale (Theoretical and Applied Genetics, 1998)

Construction of RFLP-based maps of foxtail millet, Setaria italica (L.) P. Beauv. - Z. M. Wang; K. M. Devos; C. J. Liu; R. Q. Wang; M. D. Gale (Theoretical and Applied Genetics, 1998)

Relationships between the chromosomes of Aegilops umbellulata and wheat - H. Zhang; J. Jia; M. D. Gale; K. M. Devos (Theoretical and Applied Genetics, 1998)

Comparative genetic maps of foxtail millet (Setaria italica) and rice (Oryza sativa) - K. M. Devos; Z. M. Wang; J. Beales; T. Sasaki; M. D. Gale (Theoretical and Applied Genetics, 1998)